Т. 2 - Ганецкий Я. С. Яков Станиславович; Кривцов С. С. Степан Саввич; Луначарский А. В. Анатолий Васильевич; Мещеряков Н. Л. Николай Леонидович; Ольминский М. С. Михаил Степанович (1933, 1933)
Раздельная пагинация страниц